The Effects of Tongue Twisters on Improving Pronunciation Proficiency among Eleventh-Grade Students - Sarah Suciati; Hastini Hastini; Zarkiani Hasyim; Abd. Kamarrudin (Hasanuddin University, 2025)
This study aims to determine whether the effect of tongue twisters can improve the pronunciation of eleventh-grade students at SMA Negeri 1 Lembo. A quasi-experimental design was employed with a sample of 64 students selected using random sampling techniques. Random sampling was chosen to reduce bias, produce a representative sample, facilitate statistical analysis, and allow for replicability of the research. Data were collected through writing tests administered twice as pre-test and post-test. The pre-test was given to the experimental group before the treatment, while the post-test was administered afterward. The researcher collected and analyzed the data using the formula proposed by (Cohen et al., 2007) and SPSS 22. The results indicated a significant improvement in the pronunciation scores of the experimental group, with a pre-test average of 51.56 and a post-test average of 77.97. In contrast, the control group showed a smaller improvement. The Mann-Whitney test revealed a significant difference between the two groups (p < 0.05), indicating that innovative teaching methods can enhance students' pronunciation skills. These findings suggest integrating interactive activities into English language teaching, and training for teachers is necessary to implement this method effectively. The study also opens up opportunities for further exploration of other variations of games in teaching pronunciation.